Frieren : beyond journey's end. Volume 11 - Yamada, Kanehito (Shōnen Sandē komikkusu., 2024)
"Frieren has broken the curse of Diagoldze and released herself and Denken. Now they face Macht and Solitär in a final battle of retribution. With his memories of his wife driving him, Denken challenges Macht, his former master. Frieren takes on Solitär, who is confident of victory. But demons have always underestimated Frieren, one of the greatest mages to ever live, and Macht and Solitär would do well to not count Frieren out just yet!"--Provided by publisher.